Influence of aging on dermal elastin fiber architecture and skin firmness assessed by finite element modeling - Fei Jiang; Takeshi Tohgasaki; Mayuko Kami; Ryota Sanuki; Yuya Nakata; Shinya Kondo; Xian Chen (Scientific Reports)
Abstract Skin firmness and elasticity are largely determined by the dermal extracellular matrix, particularly the elastin fiber network. Age-related degradation of elastin alters its architecture, contributing to diminished skin resilience. However, the quantitative relationship between elastin fiber geometry and macroscopic skin firmness remains incompletely understood. In this study, we developed a novel computational framework integrating realistic 3D elastin fiber geometries–extracted from confocal microscopy images of human abdominal skin samples (Caucasian females, aged 38–78 years)–into a finite element (FE) model of the dermal matrix. The elastin networks were explicitly represented as beam elements within the FE domain. Unconfined compression simulations were conducted to evaluate skin’s elastic resistance force and correlate it with quantified geometric parameters of the elastin networks. The results revealed a significant age-dependent decline in skin firmness, strongly associated with reductions in fiber diameter, fiber count, volume fraction, network connectivity (as indicated by increased fragmentation and reduced maximum cluster size), and the proportion of vertically oriented fibers. Among these, fiber count and maximum cluster size were the most important predictors of skin firmness. This study provides quantitative, mechanistic insights into how specific architectural alterations in elastin fibers directly impact the mechanical properties of aging skin. These findings emphasize the critical role of elastin network integrity and structural organization in maintaining skin function and offer a compelling rationale for therapeutic or cosmetic strategies aimed at preserving or restoring the elastin framework to maintain skin firmness.